The effects of programmed training on development of explosive strength in female volleyball players - Uzunovic, S.; Dordevic, N.; Nikolic, D.; Stošic, D.; Markovic, J.; Petrovic, V.; Kostic, L. (Facta Universitatis: Series Physical Education and Sport, 2017)
This study was done with the aim of determining the effects a programmed training would have on the changes in the explosive strength of young female volleyball players. The sample consisted of 30 female volleyball players, aged 14 to 16, divided into two groups - the experimental one (n=15) and the control group (n=15). The experimental group was comprised of the players from the club OK `Desetka`, who, apart from the basic technical and tactical training process, underwent a specially designed programme for developing explosive strength two times a week (on Tuesdays and Thursdays). The experimental programme was applied during the period of preparations before the official beginning of the regional competitions for cadets. The control group was comprised of the players from the club OK `Millennium`, who, during the same period of time, underwent only those training sessions which had previously been planned within the annual plan and programme of the club. Explosive strength evaluation included four sets of tests: the squat jump (SJ), countermowement jump (CMJ), drop jump (DJ), one-legged CMJ (OLCMJ). The effects of the progremmed training on the development of the explosive strength of the young female volleyball players was determined by the Covariance Analysis, ANCOVA. The results obtained in such a way showed the statistically significant improvement in the parameters tested within the experimental group. The difference was insignificant in the OLCMJ test only. The results point to the conclusion that the experimental training programme had positive effects on the changes of explosive strength of young female volleyball players.